Referenčne in diskurzivne vloge portugalskega nesestavljenega prihodnjika v indikativu v pripovednem besedilu Budapeste - Müller Pograjc, Blažka (Ars et humanitas, 2017)
The key aim of this paper is to shed new light on the reference and discursive roles of the verbal paradigm future tense in the indicative (futuro simples do indicativo) in Brazilian Portuguese in the narrative text Budapeste (Budapest) by Chico Buarque. A further aim is to describe the characteristics of the text environment in the sequences in which the occurrence of the future tense is detected. In order to realize this goal, it is imperative to demonstrate the common characteristics of the text environments that enable the occurrence of the future tense with its temporal and modal values and, furthermore, its discursive roles. Although Budapest is a narrative text which is particularly marked by the verbal paradigms of the past series, in four text sequences seven occurrences of the future are present. Based on an analysis of these sequences, it could be claimed that the occurrence of the future tense signals that the narrative is oriented to the present sphere of the narrator, and thus to a moment of storytelling. By considering this transition, characterized also by the presence of the future tense marking the temporal values of "futurity" and the modal values of "certainty" and "non-realisation", it can be observed that it occurs in the text sequences of Budapest within various narrative strategies. There is thus to be considered the transition from the narration to the description, the description in the descriptive sequence, and the dialogues in the dialogue fragment when the narrator uses the process of integrating the direct discourse of the protagonists in the narration.
Keywords: brazilska portugalščina; Buarque, Chico: Budimpešta; indikativ; nesestavljeni prihodnjik; pripovedni postopek